Protease concentration in amniotic fluid at term and early childhood respiratory symptoms. (23rd July 2013) - Turner, Steve W.; Carter, Jane; Danielian, Peter; Chalmers, Iain; McConaghy, Laura; Pacitti, Nicandro; Booth, Nuala
Abstract: Objective : Asthma is a common chronic disease associated with altered proteolytic activity. The present study tested the hypothesis that altered protease concentration in amniotic fluid (AF), an index of airway fluid at birth, precedes early cough and wheeze. Methods : AF was collected and analysed for the following: matrix metalloproteinases (MMP) -2, -8 and -9, tissue inhibitor of metalloproteinases (TIMP) -1 and 2, plasminogen activator inhibitor (PAI)-1. Infant were followed up at ages 1, 2 and 3 years. Results : Samples of AF were obtained in 92 infants. There were inconsistent and relatively small differences in some analytes between those individuals with and without symptoms at ages one and two years. PAI-1 concentrations were reduced in association with cough at age 1 year ( p = 0.035). Reduced MMP-8:TIMP-2 ratio was associated with wheeze at age 2 years ( p = 0.038). There were no associations between AF analytes and symptoms at 3 years of age. Conclusion : There is heterogeneity in concentrations of proteases and their inhibitors in airways at birth but in this exploratory study, there was no consistent evidence that protease concentration at birth was important to later respiratory symptoms.